An innovative approach to evidence pathways in a reactional mechanism of heterogenous catalysis - Cabanis, Tristan; Auroux, Aline; Dubois, Jean-Luc; Sbirrazzuoli, Nicolas; Postole, Georgeta (Applied catalysis, O, Open, 2025)
In this study, a pulse catalytic test set inside a microcalorimeter has been developed for studying the different steps of the heterogeneous catalytic mechanism of isopropanol dehydration to propylene. Adsorption of reactants and desorption of products are studied from an energetic point of view at temperatures in the range of 125 to 250 °C, and over commercial alumina catalyst. Results are discussed in terms of heats of adsorption, reaction and desorption of the gaseous reagent and products on the active sites of the catalyst surface. Isopropanol conversion and kinetic analysis of calorimetric signals are investigated. Heat flow signals were analyzed both at low temperature (125 °C) when only adsorption/desorption occurs, and at high temperature (>175 °C) with occurrence of adsorption, reaction and desorption. Strong dissociative adsorption was refuted from the different process steps. Meaningful kinetic parameters gave insight into the limiting steps and the reaction mechanism by analyzing the exothermic and endothermic contribution separately. Two models were used to fit the calorimetric signals, and two possible surface mechanisms are discussed: the second order elimination (E2) and the first order elimination through a carbanion path (E1cb). [Display omitted] •Dehydration of isopropanol to propylene as a sustainable alternative to fossil fuels.•Catalytic pulse test set inside a microcalorimeter for adsorption/reaction energetic studies.•Advanced kinetic computation and modelling of surface reaction mechanism.